2012
DOI: 10.1176/appi.ps.201100125
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Effects of Wellness Recovery Action Planning on Depression, Anxiety, and Recovery

Abstract: Training in mental illness self-management reduced depression and anxiety and improved participants' self-perceived recovery over time. Results confirmed the importance of WRAP as part of a group of evidence-based, recovery-oriented interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 19 publications
(12 reference statements)
3
70
2
1
Order By: Relevance
“…The intervention aimed to simultaneously diminish symptoms of depression and promote the separate dimension of well-being and life satisfaction. It achieved positive outcomes across both of these domains, similar to results among individuals with serious mental illness (50). Peer providers serve as important coping role models for both of these processes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The intervention aimed to simultaneously diminish symptoms of depression and promote the separate dimension of well-being and life satisfaction. It achieved positive outcomes across both of these domains, similar to results among individuals with serious mental illness (50). Peer providers serve as important coping role models for both of these processes.…”
Section: Discussionsupporting
confidence: 57%
“…The manualized self-management group program was adapted from the cognitive-behavioral therapy program used in our pilot study (48) and supplemented with recoveryoriented content (49,50). [The content of weekly classes is summarized in an online supplement to this article.]…”
Section: Interventionmentioning
confidence: 99%
“…WRAP also encourages participants to incorporate safe and affordable natural supports into plans that they can follow to maintain wellness. Compared with controls, WRAP participants in our earlier study (Cook, Copeland, Floyd et al, 2012) reported greater confidence that they had a plan in place to help them maintain wellness. Such confidence in one's WRAP plan may reduce participants' perceived need for formal services.…”
Section: Discussionmentioning
confidence: 64%
“…The Wellness Recovery Action Plan, or WRAP, (Cook et al, 2012) is compatible with the values and goals of feminist therapy and also has been found to be effective for individuals living with serious mental illness. Feminist therapists can recommend WRAP as an intervention that will allow them to learn better coping skills.…”
Section: Recommendations For Feminist Therapistsmentioning
confidence: 99%